Material Discord: Digitally Crafting Knitwear - Daley, Marina Jane (Auckland University of Technology, 2019)
This practice-led research explores the idiosyncratic materiality of knitted fabrications and investigates how identifying and analysing perceived redundancies in the making process has the potential to uncover new perspectives and processes that lead to innovative designs. The project employs knitted textiles and garments, which have been developed using Shima Seiki digital knitting technology, with the textile as the lead component of the design outcome. In the course of the textile’s transition from two to three dimensions, the material characteristics of the fabrication are challenged, and that results in new insights into the process for more creativity. The project’s applied nature is demonstrated in its final artefacts that of knitwear garments, but the most valuable phase for research lies in the transient states – that is to say, distortions and transparencies – that arise during fabrication. These states suggest a sense of impermanence, dissolution and regeneration. Working as a knitted textile designer-maker-technologist I have used a craft-based paradigm to illustrate an artisanal approach to digital knitwear design. Such an approach relies on the crafted aspects of irregularity and the spontaneous findings through the act of making, which gain machined effects when translated into the digital versions of themselves. However the serendipity of the crafted and hand-made inform the digital without which this final collection would not have maintained its aesthetic of decay and distortion.This communicates the importance of adopting a craft intervention and control model (Taylor and Townsend, 2014). Without being involved in designing, making and the technical aspects simultaneously, these 'failures' which informed the final aesthetic could have been overlooked. These factors are discussed in terms of an iterative design process, which oscillates between structure, aesthetic and form, while considering a place for this practice in local industry.
Keywords: Knitted Textiles; Digital Craft; Tacit Knowledge; 3-dimensional Fashion Knitwear; Digital Knit; Technology